Anthropometry and its application in the adaptation of cutting tools for workers in a pork slaughterhouse (Human Factors in Design, 2023)
Situations with potential to occupy the health of manual work can be used in the jobs of useful tools, such as, repeat, use postures, work work, mono work and use of manual application. The objective was to evaluate whether the cutting tool used in slaughterhouses meets anthropometric measurements of workers' hands. It is an applied research, with an analysis approach; as for the objectives, there is a descriptive research, with a field study design. The research carried out in a company in the field of slaughtering and processing of pork, in which 101 workers participated. Four anthropometric variables were collected from the workers' hands; Subsequently, anthropometric variables related to the work tool were verified, with the purpose of verifying whether, as measures of the direct cutting tool, affected with the anthropometric profile of direct workers. The results last that meet the facade compliance to the 95% percentile of the population. For the diameter variable, the company recommends providing knives with different sizes, among those mentioned in the literature. complains, that the company still presents facades with cables in different sizes, so that the worker has his perception in relation to the comfort and discomfort during its use.
Keywords: anthropometry; meat processing industries; work physiotherapy